The quorum sensing peptide BlpC regulates the transcription of genes outside its associated gene cluster and impacts the growth of Streptococcus thermophilus - McAnulty, Michael J.; Guron, Giselle K.; Oest, Adam M.; Miller, Amanda L.; Renye, John A. (Frontiers in Microbiology, 2024)
Bacteriocin production in Streptococcus thermophilus is regulated by cell density dependent signaling molecules, including BlpC which regulates transcription from within the bacteriocin-like peptide (blp) gene cluster. In some strains, like S. thermophilus ST106, this signaling system does not function properly and BlpC must be supplied exogenously to induce bacteriocin production. In other strains, like S. thermophilus B59671, bacteriocin (thermophilin 110 in strain B59671) production occurs naturally. Transcriptomic analyses were used to compare global gene expression within ST106 in the presence or absence of synthetic BlpC, and within B59671 to determine if BlpC regulates the expression of genes outside the blp cluster. In addition to the genes involved in bacteriocin production, BlpC affected expression of several transcription regulators outside the blp gene cluster, including a putative YtrA-subfamily transcriptional repressor. In strain B59671, BlpC regulated expression of thermophilin 110, but also suppressed the production of another bacteriocin, thermophilin 13, and induced the same YtrA-subfamily transcriptional repressor identified in ST106. Additionally, it was shown that the broad-spectrum antimicrobial activity associated with strain B59671 was due to the production of thermophilin 110, while thermophilin 13 appears to be a redundant system for suppressing intraspecies growth. BlpC production or induction negatively affected the growth of strains B59671 and ST106, revealing selective pressure to not produce bacteriocins that may explain bacteriocin production phenotype differences between S. thermophilus strains. Results from this study are expected to identify additional genes regulated by BlpC, and assist in defining conditions to optimize the production of bacteriocins for applications in agriculture or human and animal health.